ANALISIS SELF DISCLOSURE DALAM SECOND ACCOUNT DI MEDIA SOSIAL INSTAGRAM : Studi Kualitatif terhadap Second Account Instagram - Yulan Prixilia Gabrielle Silitonga, (2021)
The latest Instagram feature, second account, allows users to use two or more accounts at once on Instagram, so there is no need to log out or log in anymore. This is used by some Instagram users to have more than one account as an alter account. If the first account has clear accountability or the account name chosen is a nickname that represents itself online and offline, the second or third account is intentionally created by not representing the user's true identity. The research method used in this research is descriptive qualitative method and Johari Window concept. The informant in this study is a woman who works as a model with predetermined characteristics. Using the in-depth interview, observation and documentation method, the interactive model data analysis uses 5 aspects of Self Disclosure. As well as source triangulation, as a data validity technique. the results of this study are a form of Self Disclosure behavior mapped in the Johari Window concept. Keywords: Instagram Second account, Self-Disclosure, Johari window.